Influence of Slaughtering Ages on Carcass Characteristics, Meat Composition and Haematology of Extensively Managed Red Sokoto Bucks Slaughtered In Abeokuta Metropolis, Nigeria - Amosu Semethon David; Oderinwale Olatunde Akeem; Jolaosho Oladapo Oluwadamilare; Sanusi Ganiyu Omotayo; Oluwatosin Bamidele Omonuwa (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2017)
The study was conducted to evaluate the effects of ages at slaughtering on carcass characteristics, meat composition and haematology of extensively managed Red Sokoto bucks slaughtered in Abeokuta  Metropolis, South-Western Nigeria. A total of twenty four (24) healthy and intact Red Sokoto bucks were sourced from reputable outlets within the metropolis. The animals were grouped into ≤1 year, 1-2 years and 2-3 years of age by the means of dentition before slaughtering. The animals were slaughtered according to the method of severing the jugular veins of the throat and trachea without stunning, meat samples from various parts of the bucks were taken for proximate composition, while the haematological analysis which include: Haemoglobin, Packed cell volume, red blood cell, white blood cell, mean corpuscular volume, mean corpuscular haemoglobin, mean corpuscular haemoglobin concentration and white blood differentials was carried out. Data obtained were subjected to one-way analysis of variance using General linear model (GLM) procedures of SAS. Level of significance was taken at 5% probability, while means were separated using Duncan's Multiple Range Test of the same statistical package. Results obtained revealed that bucks within 2-3 years had highest (p<0.05) values for carcass components such as live weight (14.63%); Slaughter weight (93.16%); Dressed weight (92.96%); and Chest weight (2.6%), while bucks ≤1year had highest (p<0.05) values for Empty carcass weight (70.29%); Hot carcass weight (54.77%); and Half carcass weight (23.15%). For organs and offal components, bucks within ≤1 year had significantly (p<0.05) highest values for all the components except for lungs weight which was highest (p<0.05) for bucks within 1-2 years. Different primal cuts of the bucks were significantly (p<0.05) highest for bucks within 2-3 years, except for feet weight that was highest (p<0.05) for bucks within ≤1 year. For meat composition, meat cuts at different parts from slaughtered bucks within 2-3 years had overall best nutritive value. The haematological  parameters examined in the study were not significantly (p>0.05) affected by the age of the animals and they fell within the range for healthy animals. The result obtained from this study indicated that Red Sokoto bucks between the ages of 2-3 years can be slaughtered for high carcass yield with best nutritive value and good health condition.